Rheological, fatigue and relaxation properties of aged bitumen. Issue Volume 21:Issued 8(2020) (2nd July 2020) - Jing, Ruxin; Varveri, Aikaterini; Liu, Xueyan; Scarpas, Athanasios; Erkens, Sandra
ABSTRACT: Bitumen ageing has a significant impact on the mechanical performance of asphalt concrete. This study utilises dynamic mechanical tests (frequency sweep, fatigue, and relaxation) to investigate the effect of ageing on the viscoelastic characteristics of bitumen. As ageing progressed, a shift of the Black diagrams curves towards lower phase angles was observed; at the same time the shape of the curves changed to a straight line and the curvature reduced. Interestingly, based on the standard fatigue analysis criteria, ageing appears to have a positive effect on bitumen fatigue life. Consequently, it occurs that studying only the stiffness and fatigue behaviour of bitumen cannot directly characterise ageing-induced degradation. The stress relaxation test was found to be more suitable to characterise ageing of bitumen. Aged bitumen had higher residual stresses and longer relaxation times. Hence, aged bitumen was found to be more susceptible to stress accumulation and thus cracking. A linear relationship was established between the crossover modulus and the stress relaxation ageing indices for the studied bitumen. This relationship suggests that crossover modulus has the potential to be used as a parameter to characterise the bitumen relaxation properties by means of routine tests such as the DSR frequency sweep tests.